Antioxidant and Anti-atherogenic Properties of Prosopis strombulifera and Tessaria absinthioides Aqueous Extracts: Modulation of NADPH Oxidase-Derived Reactive Oxygen Species - Quesada, Isabel; de Paola, Matilde; Alvarez, María Soledad; Hapon, María Belén; Gamarra-Luques, Carlos; Castro, Claudia (Frontiers in Physiology, 2021)
Despite popular usage of medicinal plants, their effects as cardiovascular protective agents have not been totally elucidated. We hypothesized that treatment with aqueous extract from Prosopis strombulifera (AEPs) and Tessaria absinthioides (AETa), Argentinian native plants, produce antioxidant effects on vascular smooth muscle cells (VSMC) and attenuate atherogenesis on apolipoprotein E-deficient (ApoE KO) mice. In VSMC both extracts (5-40 μg/mL) inhibited 10% Fetal Calf Serum-induced cell proliferation, arrested cell in G2/M phase, reduced Angiotensin II-induced reactive oxygen species (ROS) generation and decreased NADPH oxidase subunits expression. In ApoE-KO mice, extracts significantly reduced triglyceridemia and lipid peroxidation (plasma TBARS); increased plasma total antioxidant status (TAS), and improved glutathione peroxidase activity in the liver. Under high fat diet both extracts were able to inhibit O2•(-) generation in the aortic tissue and caused a significant regression of atheroma plaques (21.4 %±1.6 HFD group vs 10.2%±1.2* AEPs group and 14.3%±1.0* AETa group; *P<0.01). Consumption of AEPs and AETa produces anti-oxidant/anti-mitogenic/anti-atherosclerotic effects and their use may be beneficial as a complementary strategy regarding cardiovascular diseases therapies.